BLOCKING AND EXTENDED EXPONENCE OF SUFFIX PRONOUNS IN ARABIC PERFECTIVE VERB CONJUGATION - Mardiah, Zaqiatul; Hizbullah, Nur; Niswah, Awaliyah Ainun (UI Scholars Hub, 2020)
Noyer (1997) utilized blocking and extended exponence to encode pronouns in the conjugation of imperfect verbs in Arabic. His findings were criticized by Stump (2001) and Xu (2010), because the formulation was considered too complex. Xu (2010) offered a unified integrated account based on Optimality Theory while still relying on blocking and extended exponence. However, their for-mulation only focuses on the pronouns of imperfect verb conjugations. So far, the optimality of conjugations of perfective Arabic verbs which are also complex in nature, have not been considered yet in their studies. This study extends the work of Xu (2010) by developing the formulation of the optimal forms of the suffix pronouns of the Arabic perfective verb conjugations. The results of study reveal that several exponences which in different situations, each can realize several assingments. Instead, there is an assignment that is realized by more than one exponen